Creative Human-Robot Co-Manipulation. - Allen, Katherine H. (Tufts University. Tisch Library., 2025)
Keywords: assistive technology, human-robot interaction, manipulation, robotics.; Topic: Applied computing / Physical sciences and engineering / Engineering; Topic: Human-centered computing / Human computer interaction (HCI) / HCI design and evaluation methods / User studies; Topic: Hardware / Emerging technologies / Emerging interfaces; ACM Open.